The Glaciations in South America - Poire, Daniel Gustavo; Gómez Peral, Lucia; Arrouy, Maria Julia
Neoproterozoic successions in South America are recorded in many areas of Brazil, Paraguay, Bolivia, Uruguay and Argentina. Some of these units show glaciogenic formations like those represented in the Puga and Serra Azul formations in the Northern Paraguay Belt (Brazil) in agreement with their accumulation in a Snowball Earth context. However, in other cases, tillites or other glaciomarine deposits are absent, which may indicate a distant position (tropical) regarding the ice cap, as occurs in the Tandilia System (Argentina) related to a ?Phantom glacial? context. In this contribution we show the comparison between direct and indirect evidence of glaciations in the Neoproterozoic successions of South America. The Puga and Serra Azul formations in the Paraguay Belt and Sierras Bayas Group in the Río de la Plata Craton have been chosen to describe the ?Snowball Earth? and ?Phantom glacial? models, respectively. By means of multiproxy analysis it is also possible to indicate changes in paleoclimate conditions in both cases. The presence of tillites is considered to be direct evidence of the extreme climatic conditions during deposition during a glaciation. Meanwhile, more subtle evidence such as regional unconformities related to drastic sea level changes, trends in δ13C, events of phosphogenesis, constitute, among others, the tools to indicate the influence of Neoproterozoic global glaciations during the deposition of the sedimentary units. Fil: Poire, Daniel Gustavo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigaciones Geológicas. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Investigaciones Geológicas; Argentina Fil: Gómez Peral, Lucia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigaciones Geológicas. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Investigaciones ...